Dlx5 and Mef2 Regulate a Novel Runx2 Enhancer for Osteoblast‐Specific Expression. (September 2014) - Kawane, Tetsuya; Komori, Hisato; Liu, Wenguang; Moriishi, Takeshi; Miyazaki, Toshihiro; Mori, Masako; Matsuo, Yuki; Takada, Yoshio; Izumi, Shinichi; Jiang, Qing; Nishimura, Riko; Kawai, Yosuke; et al.
ABSTRACT Runx2 is essential for osteoblast differentiation and chondrocyte maturation. The expression of Runx2 is the first requisite step for the lineage determination from mesenchymal stem cells to osteoblasts. Although the transcript from Runx2 distal promoter is majorly expressed in osteoblasts, the promoter failed to direct green fluorescent protein (GFP) expression to osteoblasts. To find the regulatory region, we generated GFP reporter mice driven by a bacterial artificial chromosome (BAC) of Runx2 locus, and succeeded in the reproduction of endogenous Runx2 expression. By serially deleting it, we identified a 343‐bp enhancer, which directed GFP expression specifically to osteoblasts, about 30 kb upstream of the distal promoter. The sequence of the 343‐bp enhancer was highly conserved among mouse, human, dog, horse, opossum, and chicken. Dlx5, Mef2c, Tcf7, Ctnnb1, Sp7, Smad1, and Sox6, which localized on the enhancer region in primary osteoblasts, synergistically upregulated the enhancer activity, whereas Msx2 downregulated the activity in mouse osteoblastic MC3T3‐E1 cells. Msx2 was predominantly bound to the enhancer in mouse multipotent mesenchymal C3H10T1/2 cells, whereas Dlx5 was predominantly bound to the enhancer in MC3T3‐E1 cells. Dlx5 and Mef2 directly bound to the enhancer, and the binding sites were required for the osteoblast‐specific expression in mice, whereas the other factors bound to the enhancer by protein‐protein interaction. The enhancer was characterized by the presence of the histone variant H2A.Z, the enrichment of histone H3 mono‐ and dimethylated at Lys4 and acetylated at Lys18 and Lys27, but the depletion of histone H3 trimethylated at Lys4 in primary osteoblasts. These findings indicated that the enhancer, which had typical histone modifications for enhancers, contains sufficient elements to direct Runx2 expression to osteoblasts, and that Dlx5 and Mef2, which formed an enhanceosome with Tcf7, Ctnnb1, Sp7, Smad1, and Sox6, play an essential role in the osteoblast‐specific activation of the enhancer. © 2014 American Society for Bone and Mineral Research.